The meaning of sex genes [and] gender - Barbara J. Meyer, lecturer; David C. Page, lecturer; Howard Hughes Medical Institute (Chevy Chase, MD Howard Hughes Medical Institute, 2003)
Why does sex exist, and what is its purpose and function? What decides whether an individual will be male of female? How are chromosomes, genes, and molecules involved in determining sex? In four lectures, two leading scientists in the field of sex-determination research answer these questions.
Lecture 1. Deciphering the language of sex -- lecture 2. Hermaphrodities, the safer sex -- lecture 3. Sex and death, too much of a good thing -- lecture 4. Sexual evolution, from X to Y.
Howard Hughes Medical Institute holiday lectures on science, November 2001.
Keywords: Sex Determination Processes; Gene Expression Regulation; Sex Chromosomes; Sex determination (Genetics).